Diffusion Tensor Imaging Tractography of the Facial Nerve in Patients With Cerebellopontine Angle Tumors. Issue 4 (April 2016) - Hilly, Ohad; Chen, Joseph M.; Birch, James; Hwang, Euna; Lin, Vincent Y. W.; Aviv, Richard I.; Symons, Sean P.
Abstract : Objective: To demonstrate the utility of diffusion tensor imaging (DTI) fiber tractography of the facial nerve in patients with cerebellopontine angle (CPA) tumors. Study Design: Prospective. Setting: Tertiary referral center. Patients: DTI technique was established in 113 patients without tumors and in 28 patients with CPA tumors. Subsequently, DTI results were compared with intraoperative findings in 21 patients with medium and large-sized tumors, treated surgically via a translabyrinthine approach. Intervention: Three Tesla magnetic resonance (MR) was used for DTI tractography. For patients without CPA tumors, the scanning protocol was 32 directions with a 3 × 3 × 3 mm voxel size. For CPA tumor patients, scanning protocol was 32 directions with a 2 × 2 × 2 mm voxel size. DTI data were used to track the facial nerve. Main Outcome Measures: Facial nerve identification rate. Results: Facial nerve identification rate in MR-DTI was 97% and 100% in patients without tumors and in patients with tumors of the CPA of the internal auditory canal that were not treated surgically, respectively. MR-DTI identification of the facial nerve was successful in 20 patients who were treated surgically (95%). Good agreement between surgical findings and MR-DTI results was found in 19 patients (90%). Conclusion: MR DTI tractography is an effective technique in positively identifying the position of the facial nerve in patients with CPA tumors.